2021
DOI: 10.4155/fdd-2020-0034
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of advanced in vitro and ex vivo cancer models for disease modeling and drug screening

Abstract: Bioengineered in vitro models have advanced from 2D cultures and simple 3D cell aggregates to more complex organoids and organ-on-a-chip platforms. This shift has been substantial in cancer research; while simple systems remain in use, multi-tissue type tumor and tissue chips and patient-derived tumor organoids have grown rapidly. These more advanced models offer new tools to cancer researchers based on human tumor physiology and the potential for interactions with nontumor tissue physiology while avoiding cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…[22][23][24][25] Previous efforts showed that 3D bioprinting technology can be used to arrange tumor spheroids and organoids for various applications like drug screening and tissue engineering. [26][27][28][29][30][31][32][33][34] Although 3D bioprinting technology can achieve multi-size, multi-material, and multi-cell printing tasks, it limits in the precise construction. [22,[35][36][37] Here, we used an acoustic bioprinting device to precisely arrange colorectal cancer (CRC) and healthy organoids into 3D architecture for mimicking the diseased colorectum of patient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25] Previous efforts showed that 3D bioprinting technology can be used to arrange tumor spheroids and organoids for various applications like drug screening and tissue engineering. [26][27][28][29][30][31][32][33][34] Although 3D bioprinting technology can achieve multi-size, multi-material, and multi-cell printing tasks, it limits in the precise construction. [22,[35][36][37] Here, we used an acoustic bioprinting device to precisely arrange colorectal cancer (CRC) and healthy organoids into 3D architecture for mimicking the diseased colorectum of patient.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22–25 ] Previous efforts showed that 3D bioprinting technology can be used to arrange tumor spheroids and organoids for various applications like drug screening and tissue engineering. [ 26–34 ] Although 3D bioprinting technology can achieve multi‐size, multi‐material, and multi‐cell printing tasks, it limits in the precise construction. [ 22,35–37 ]…”
Section: Introductionmentioning
confidence: 99%